Existential injustice in phenomenological psychopathology - Vespermann, Daniel; Tirkkonen, Sanna K. (Philosophical psychology, 2025)
In this article, we investigate how distressing background feelings can be subject to social injustice. We define background feelings as enduring feeling states that condition our perceptions of everyday situations, interpersonal dynamics, and the broader social milieu. While phenomenological psychopathology has long addressed such affective phenomena, including anxiety, guilt, and feelings of not belonging, the intersection with social injustice remains largely unexplored within the framework. To address this gap, we introduce the concept of existential injustice into phenomenological psychopathology. Existential injustice pertains to the unjust formation, perpetuation, and treatment of background feelings. We contend that distressing alterations in these feeling states can stem from, or be perpetuated by, unjust social structures and practices. Existential injustice manifests as a felt inadequacy of one’s background feelings, reflecting broader societal disparities and inequities. Drawing on themes from social psychiatry, we illustrate the utility and explanatory power of the concept through two concrete examples. By shedding light on the ways in which societal dynamics shape distressing affective experiences our analysis underscores the importance of integrating aspects of social injustice into the study of affective phenomena in phenomenological psychopathology.
Online veröffentlicht: 30. September 2024
Gesehen am 26.02.2025